Reversal of Sjögren's-like syndrome in non-obese diabetic mice. Issue 6 (19th December 2006) - Tran, Simon D; Kodama, Shohta; Lodde, Beatrijs M; Szalayova, Ildiko; Key, Sharon; Khalili, Saeed; Faustman, Denise L; Mezey, Éva
Abstract : Background: Non-obese diabetic (NOD) mice exhibit autoimmune diabetes and Sjögren's-like syndrome. Objective: To test whether a treatment that reverses end-stage diabetes in the NOD mouse would affect their Sjögren's-like syndrome. Methods: NOD mice have a proteasome defect. Improperly selected naive T cells escape, but can be killed by reintroducing major histocompatibility complex class I self-peptides on matched normal splenocytes. The proteasome defect also impairs nuclear factor kB, a transcription factor in pathogenic memory T cells, increasing their susceptibility to tumour necrosis factor-induced apoptosis stimulated through complete Freund's adjuvant (CFA). The impact of this two-limb therapy (injections of matched normal splenocytes and CFA) on the autoimmune salivary gland disease of the NOD mice was studied. Results: All NOD mice receiving the above treatment had a complete recovery of salivary flow and were protected from diabetes. Restoration of salivary flow could be the result of a combination of rescue and regeneration of the gland, as confirmed by immunohistochemical analysis. All untreated NOD mice showed a continuous decline in salivary flow, followed by hyperglycaemia and death. Conclusion: This study establishes that a brief intervention in NOD mice with Sjögren's-like syndrome can reverse salivary gland dysfunction.